Decarbonizing an industrial process through a combined, high-temperature CSP and sensible heat storage - Martín-Alcántara, Antonio; Serrano-Aguilera, Juan José; Sánchez Sánchez de Puerta, Álvaro; Aranda Hidalgo, José Luis (Elsevier, 2024)
Decarbonization is crucial to meet global environmental goals by 2050 and combating climate change. The current work studies a thermal system combining CSP (solar dish) and thermal energy storage (TES) technologies aimed at reducing CO2 emissions. Given the Direct Normal Irradiance (DNI) profiles of two southern Spain locations (Córdoba and Málaga), numerical simulations have been conducted to analyze the power and the energy provided by this proof of concept on three representative days of 2022 (two solstices and one equinox). One or several solar dishes first increase the temperature of the heat transfer fluid (HTF). Then, following a simple decision-making algorithm, the mass flow enters or bypasses a TES unit. If additional backup energy is required to reach a final temperature, it is supplied externally from e.g. electric sources. A sensitivity analysis has shown that four solar dishes in parallel configuration, combined with a TES unit of aspect ratio L/D=1.5 (if in Córdoba) or L/D=1.0 (if in Málaga), is a suitable solution to effectively reduce the external energy consumed by the system as well as the operation cost and the environmental impact. This study is completed with the calculation of the levelized cost of heat (LCOH), resulting in a favorable economic viability compared to other heating plants.
Keywords: Energía térmica; Decarbonization; Numerical simulation; Solar dish (CSP); Thermal energy storage (TES); High-temperature heat; Levelized cost of heat (LCOH)